(untitled) (Research, Society and Development, 2023)
Objective: To point out the challenges and prospects for maintaining the longitudinal care offered to patients with hypertension and diabetes in the Family Health Strategy from the perspective of medical students. Methodology: This is an experience report based on an intervention project carried out with a family health team in the municipality of Eunápolis, Bahia, and patients with hypertension and diabetes. Results: The multiprofessional team working in the health unit provided 33 consultations. The action developed was based on the interest of the patients in taking part in activities offered by trained health professionals, such as operational groups focused on conditions such as diabetes and hypertension. Conclusion: We noted the importance of medical students working in the Family Health Strategy to strengthen the relationship between the health team and the community, which facilitates the promotion of preventive actions that are important for the effectiveness of longitudinal care for users. This contributes both to the integrality proposed by the Unified Health System and to improving more humanized care in Primary Health Care.